High-speed jaw-opening exercise in training suprahyoid fast-twitch muscle fibers - Matsubara M (Dove Medical Press, 2018)
Mariko Matsubara,1,2 Haruka Tohara,1 Koji Hara,1 Hiromichi Shinozaki,1 Yasuhiro Yamazaki,1 Chiaki Susa,1 Ayako Nakane,1 Yoko Wakasugi,1 Shunsuke Minakuchi1 1Gerodontology and Oral Rehabilitation, Department of Gerontology and Gerodontology, Graduate School of Medical and Dental Sciences, Tokyo Medical and Dental University, Tokyo, 2Department of Oral Surgery, Ichigao Carillon Hospital, Kanagawa, Japan Purpose: This study was aimed to examine the effectiveness of a high-speed jaw-opening exercise, which targets the contraction of fast-twitch muscle fibers, in improving swallowing function.Subjects and methods: Twenty-one subjects (mean age 74.0±5.7 years) with dysphagia-related symptoms, such as coughing or choking during eating, performed the exercise. None of the included subjects had neurological symptoms or history of surgery that could cause significant dysphagia. All subjects took regular meals, and maintained independent activities of daily life. The exercise schedule consisted of 3 sets of 20 repetitions each of rapid and maximum jaw-opening movement with a 10-second interval between sets. The exercise was performed twice daily for 4 weeks.Results: Following the intervention, there was a significant increase in the vertical position of the hyoid bone at rest. Furthermore, during swallowing, the elevation of the hyoid bone and the velocity of its movement and esophageal sphincter opening increased significantly while the duration of the hyoid elevation and the pharyngeal transit time reduced significantly.Conclusions: Our results demonstrated that high-speed jaw-opening exercise resulted in increased elevation velocity of the hyoid bone during swallowing, indicating its role in effectively strengthening the fast-twitch muscle fibers of suprahyoid muscles. Furthermore, since the rest position of the hyoid bone appeared to have improved, this exercise may be especially useful in elderly individuals with a lower position of the hyoid bone at rest and those with decreased elevation of the hyoid bone during swallowing, which are known to be associated with an increased risk of aspiration. Keywords: deglutition disorders, jaw, exercise, rehabilitation, fast-twitch muscle fibers, high speed